2022
DOI: 10.1002/jcla.24603
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a time‐resolved immunoassay for acute kidney injury based on the detection of Kim‐1

Abstract: Aim To establish a highly sensitive time‐resolved fluorescence immunoassay (TRFIA) of kidney injury molecule‐1 (Kim‐1) and evaluate its clinical value in acute kidney injury (AKI). Methods The Kim‐1‐TRFIA was established by the double‐antibody sandwich method, and the method was evaluated. The established Kim‐1‐TRFIA was used to detect the concentration of Kim‐1 in the serum of healthy controls and patients with AKI. Results The optimal coati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…In addition, no cross-reactivity of other nephrotic biomarkers was observed. In previous studies, Kim-1-TRFIA showed a good correlation with Kim-1-ELISA ( Shaoxiong et al, 2022 ); in the present experiment, the results of Kim-1-TRFIA and Kim-AlphaLISA showed a good correlation ( R 2 = 0.9086). Thus, the developed method can be used to detect Kim-1 levels in serum and urine in clinical conditions and provide reliable, accurate, and stable results.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…In addition, no cross-reactivity of other nephrotic biomarkers was observed. In previous studies, Kim-1-TRFIA showed a good correlation with Kim-1-ELISA ( Shaoxiong et al, 2022 ); in the present experiment, the results of Kim-1-TRFIA and Kim-AlphaLISA showed a good correlation ( R 2 = 0.9086). Thus, the developed method can be used to detect Kim-1 levels in serum and urine in clinical conditions and provide reliable, accurate, and stable results.…”
Section: Discussionsupporting
confidence: 74%
“…Shao ( Shao et al, 2014 ) et al estimated the diagnostic sensitivity and specificity of Kim-1 in AKI to be 74% and 86%, respectively. AKI is an increasingly frequent disease as part of acute kidney disease, defined clinically as a rapid loss of kidney function ( Liu et al, 2020 ; Shaoxiong et al, 2022 ), which can be fatal if not treated promptly ( Geng et al, 2021 ). AKI has been reported to be a common complication in hospitalized and critically ill patients ( Vijayan et al, 2021 ), and it can be induced by a variety of risk factors, such as sepsis, cirrhosis, acute pancreatitis, cancer, chronic kidney disease, COVID-19, and cardiac surgery ( Campbell et al, 2014 ; Gaffney and Sladen, 2015 ; Nassar and Qunibi, 2019 ; Gupta et al, 2021 ; Kuwabara et al, 2022 ; Wu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations